FRI0275 Altered protein tyrosine phosphatases activity and disease specific expression pattern of cd45 and cd148 on various lymphocyte subsets in autoimmune diseases. (12th June 2018) - Szelinski, F.; Fleischer, S.; Weißenberg, S.; Reiter, K.; Dörner, T.
Abstract : Background: Previous studies demonstrated impaired B cell receptor (BCR) response in patients with systemic lupus erythematosus (SLE). Besides diminished cytokine production upon TLR9 stimulation 1 it was found that phosphorylation of Syk 2 and downstream Ca +2 flux was reduced upon BCR stimulation. This led to the hypothesis of a "post activation" state of peripheral B cells (BCs) in autoimmunity which might be related to altered protein tyrosine kinase (PTK) versus phosphatase (PTP) activities. Prior studies in SLE showed enhanced PTP but not ser/thr phosphatase (PSP) activities in BCs. 3 Receptor PTPs (RPTPs) CD45/CD148 are described as regulators of initial steps of BCR signalling by regulating Lyn which phosphorylates CD79 ITAMs and thus activates Syk. 4 Objectives: This study aimed at testing the hypothesis that altered phosphatase activity (PA) is a hall mark of autoimmunity. So, expression of RPTPs CD45/CD148 were compared on lymphocyte subsets in patients with rheumatoid arthritis (RA), primary Sjögren's Syndrome (pSS), SLE and healthy donors (HD). To check whether increased global PA is restricted to BCs of patients with SLE, the study extended analysis to T cells (TCs) and studied patients by including cohorts of RA and pSS. Methods: Peripheral blood samples were analysed for expression of CD45 and CD148 in patients and HDs using flow cytometry (n(HD/RA/pSS/SLE)=13/8/18/22). PTP and PSP activities were analysed in isolated BCs and TCs lysates from patients and HD using a protein activity assay (n(HD/RA/pSS/SLE)=21/6/13/10). Results: Compared to HDs CD45 expression is significantly enhanced on peripheral monocytes and CD3 + /CD4 - as well as CD3 + /CD4 + TCs from patients with RA. Further, CD3 + /CD4 - TCs of patients with RA express more CD148 (Tbl 1). In patients with SLE, CD148 expression is decreased on CD148 + memory B cells. In addition, this study confirmed that enhanced PTP activity is characteristic of SLE BCs since TCs of any of the cohorts and BCs of patients with RA and pSS showed PTP and PSP activities comparable to HD. Conclusions: This study identified characteristic differences of PTP activities in BCs from patients with SLE compared to HD which were not identifiable by an enhanced CD45 or CD148 expression on PBMCs and did not correlate with disease activity. This suggests intrinsic abnormality in SLE BCs. While there is evidence that abnormal PTP is present in SLE BCs, further studies are needed to identify underlying individual PTPs to further analyse their pathogenic and potential therapeutic relevance. Among the tested autoimmune conditions increased CD45 expression on TCs and monocytes was specific to RA, which might indicate disease dependent patterns of PTP/PSP expression. References: [1] Sieber, et al. ArthritisResTher2014. [2] Fleischer, et al. JImmunol2013. [3] Fleischer, et al. ArthritisRheumatol2016. [4] Zhu, et al. Immunity2008. Disclosure of Interest: None declared